Efek Nefroprotektif Ekstrak Daun Kersen pada Tikus Model Nefrotoksisitas: Analisis Biokimia, Histopatologi, Antioksidan, dan Sitokin - Asyrun Alkhairi Lubis; Razoki Razoki; Novitaria Br. Sembiring; Nina Nurdiana Hasibuan; Miranda Simanjuntak; Rikki DP Turnip; Gabriella Tarigan (Journal of Pharmaceutical and Sciences, 2026)
Background: Gentamicin-induced nephrotoxicity is closely associated with oxidative stress and inflammation that lead to renal damage. Natural compounds with antioxidant and anti-inflammatory properties are potential nephroprotective agents. Muntingia calabura L. leaves are rich in bioactive compounds such as flavonoids and polyphenols. Objective: This study aimed to evaluate the nephroprotective effect of Muntingia calabura L. leaf ethanol extract in a gentamicin-induced rat model. Methods: Male Wistar rats were divided into five groups: normal control, negative control (gentamicin), and treatment groups receiving extract doses of 100, 200, and 400 mg/kgBW. Renal function, inflammatory cytokines, antioxidant activity, and histopathological changes were evaluated. Results: The extract demonstrated dose-dependent nephroprotective activity, with the 400 mg/kgBW dose showing the most optimal effect in improving renal function, reducing inflammatory responses, and preserving kidney histological structure. Conclusion: Muntingia calabura L. leaf extract exhibits nephroprotective potential through antioxidant and anti-inflammatory mechanisms, supporting its development as a natural therapeutic candidate.